2013
DOI: 10.3389/fnins.2013.00140
|View full text |Cite
|
Sign up to set email alerts
|

Circannual changes in stress and feeding hormones and their effect on food-seeking behaviors

Abstract: Seasonal fluctuations in food availability show a tight association with seasonal variations in body weight and food intake. Seasonal variations in food intake, energy storage, and expenditure appear to be a widespread phenomenon suggesting they may have evolved in anticipation for changing environmental demands. These cycles appear to be driven by changes in external daylength acting on neuroendocrine pathways. A number of neuroendocrine pathways, two of which are the endocrine mechanisms underlying feeding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 163 publications
(291 reference statements)
0
15
0
Order By: Relevance
“…Diabetic ketoacidosis results from relative or absolute insulin deficiency coupled with increased regulatory counter‐regulatory hormones . In a review of circannual hormonal changes, basal levels of glucocorticoids appear to be highest in autumn (fall) and winter and lowest in spring and summer . For example, in a study of healthy men, temporal variation was found in cortisol levels, with a peak in December .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic ketoacidosis results from relative or absolute insulin deficiency coupled with increased regulatory counter‐regulatory hormones . In a review of circannual hormonal changes, basal levels of glucocorticoids appear to be highest in autumn (fall) and winter and lowest in spring and summer . For example, in a study of healthy men, temporal variation was found in cortisol levels, with a peak in December .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barenton et al (1988) demonstrated that variation in photoperiod has a direct effect on BW: long days stimulate and short days inhibit weight gain. The HPA axis and other neuroendocrine systems may be operative in these effects in rams (Cahill et al, 2013;Ebling, 2015).…”
Section: Adaptation To Heat Reducesmentioning
confidence: 99%
“…In seasonal breeders, the potential benefits of increased food availability may be offset by greater energy expenditure through reproductive activities (Hinsch, Pen, & Komdeur, 2013). In contrast, nonbreeding animals face other metabolic challenges including: low temperatures and inclement weather (De Bruijn & Romero, 2013;Metcalfe, Schmidt, Bezner Kerr, Guglielmo, & MacDougall-Shackleton, 2013;Romero, Reed, & Wingfield, 2000); reduced food availability and less foraging time with short photoperiods (Cahill, Tuplin, & Holahan, 2013;Watts & Hahn, 2012); and longer overnight fasts (Smith, Reitsma, & Marra, 2011). Seasonal differences in energetic balance are well-documented (Fokidis, Orchinik, & Deviche, 2009;Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%